Selection of Conceptual Design Using Analytical Hierarchy Process for Automotive Bumper Beam Under Concurrent Engineering Environment - Arep @ Ariff, Hambali (2009)
The main objective of this research is to consider and determine the most optimum decision on design concept, material and manufacturing process for the automotive composite bumper beam at the conceptual design stage. The objective was achieved by proposing two selection frameworks and the use of analytical hierarchy process under concurrent engineering environment. The research began by generating and developing eight new conceptual designs of automotive composite bumper beam and investigating various parameters or criteria and alternatives that normally used to manufacture automotive composite bumper beam by implementing total design approach. To determine the most optimum decisions on design concept, material and manufacturing process for the automotive composite bumper beam, analytical hierarchy process utilizing Expert Choice software was used. The research revealed that the glass fibre epoxy with a value of 0.257 (25.7%), design concept-6 with a value of 0.191 (19.1%) and injection moulding with a value of 0.228 (22.8%) are the most appropriate decisions on material, design concept and manufacturing process respectively. It was also revealed that importance of addressing various design tools and considering the most optimum decisions on design concept, material and manufacturing process at the conceptual design stage in the design flow under concurrent engineering environment. Overall, it can be concluded that the proposed selection frameworks, analytical hierarchy process and concurrent engineering approach allow designers or decision makers to consider and determine the most optimum decision on design concept, material and manufacturing process at the conceptual design stage.